2011
DOI: 10.1007/s10346-011-0279-3
|View full text |Cite
|
Sign up to set email alerts
|

Strong ground motions from the 2011 off-the Pacific-Coast-of-Tohoku, Japan (Mw = 9.0) earthquake obtained from a dense nationwide seismic network

Abstract: Takashi Furumura I Shunsuke Takemura I Shinako Noguchi I Teito Takemoto I Takuto Maeda I Kazuhisa Iwai I Simanchal Padhy Strong ground motions from the 2011 off-the Pacific-Coast-of-Tohoku, Japan (Mw=9.0) earthquake obtained from a dense nationwide seismic network Abstract The dense recordings of the K-NET and KiK-net nationwide strong motion network of 1,189 accelerometers show clearly the radiation and propagation properties of the strong ground motions associated with the 2011 off-the-Pacific Coast-ofTohoku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 8 publications
3
26
0
4
Order By: Relevance
“…This observation suggests development of a sliding surface deeper than 0.5 m below the seafloor, which would further favor unstable sliding under such a large ground acceleration. The prolonged shaking and large ground accelerations at interval of about 50 s [ Furumura et al , 2011] also confirms our results.…”
Section: Discussionmentioning
confidence: 99%
“…This observation suggests development of a sliding surface deeper than 0.5 m below the seafloor, which would further favor unstable sliding under such a large ground acceleration. The prolonged shaking and large ground accelerations at interval of about 50 s [ Furumura et al , 2011] also confirms our results.…”
Section: Discussionmentioning
confidence: 99%
“…The dominant period of the long-period ground motions observed in the Kanto Basin tends to be approximately 7 s for shallow moderate-to-large earthquakes (e.g., Miyake and Koketsu 2005;Furumura and Hayakawa 2007;Furumura et al 2011), which is strongly controlled by the velocity structure at depths of less than 2 km (e.g., Yoshimoto and Takemura 2014b). Using seismic data from dense strong motion networks in the Kanto Basin (Kinoshita 1998;Okada et al 2004), previous studies have revealed that the long-period ground motions are generated by surface waves propagating over the thick sediments in the Kanto Basin (e.g., Koketsu and Kikuchi 2000;Miura and Midorikawa 2001;Furumura and Hayakawa 2007;Hayakawa 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Their observations suggest changes in fluid conditions such as a permeability of near-surface cracks in the upper few hundred meters beneath the surface Snieder 2011, 2012). Because the sediment layer beneath the local uplift area is thicker than in other areas (>2000-3000 m thick), which also appear as a negative Bouguer anomaly (e.g., Tada 1982), Furumura et al (2011) andFurumura (2014) have reported that the velocity response spectrum shows that the earthquake caused long seismic shear waves (~1-30 s). The geological characteristics would alter the permeability of the aquifer structure and induce pore fluid migration in the area significantly.…”
Section: Possible Mechanisms Of Local Surface Upliftmentioning
confidence: 99%